2017
DOI: 10.1186/s13024-017-0183-y
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and inflammation in the central nervous system

Abstract: Persistent endoplasmic reticulum (ER) stress is thought to drive the pathology of many chronic disorders due to its potential to elicit aberrant inflammatory signaling and facilitate cell death. In neurodegenerative diseases, the accumulation of misfolded proteins and concomitant induction of ER stress in neurons contributes to neuronal dysfunction. In addition, ER stress responses induced in the surrounding neuroglia may promote disease progression by coordinating damaging inflammatory responses, which help f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
166
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(187 citation statements)
references
References 216 publications
(232 reference statements)
4
166
0
1
Order By: Relevance
“…Recent studies have suggested that endoplasmic reticulum stress (ERS) plays an essential role in inflammatory responses, and is involved in the pathological process of inflammatory diseases. 9,10 The ERS downstream pathway inositol-requiring kinase 1 (IRE1) regulates apoptosis via the ASK1-c-terminal kinase (JNK) pathway. 11 Therefore, ASK1 is correlated with ERS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that endoplasmic reticulum stress (ERS) plays an essential role in inflammatory responses, and is involved in the pathological process of inflammatory diseases. 9,10 The ERS downstream pathway inositol-requiring kinase 1 (IRE1) regulates apoptosis via the ASK1-c-terminal kinase (JNK) pathway. 11 Therefore, ASK1 is correlated with ERS.…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed overt ER stress in the myocardium following LPS-induced endotoxaemia. ER stress has been shown to contribute to neurodegenerative disorders and ischaemia reperfusion-induced cardiac damage [21,22]. Our data revealed upregulated expression of the ER chaperone Grp78, which directly interacts with all three ER stress sensors, eIF2a, Gadd153, and IRE1a in sepsis.…”
Section: Discussionmentioning
confidence: 62%
“…Neuropathic symptoms in COPA syndrome have also not been widely reported previously; however, all three of the patients in this report manifested with various neural symptomatology. ER stress has been linked with central nervous system inflammation and neuronal dysfunction [16] and may be another aspect of the broader COPA syndrome phenotype.…”
Section: Discussionmentioning
confidence: 99%